Corrosion behaviour of friction stir-welded AA6005-T6 using a bobbin tool. (October 2016) - Esmaily, M.; Mortazavi, N.; Osikowicz, W.; Hindsefelt, H.; Svensson, J.E.; Halvarsson, M.; Thompson, G.E.; Johansson, L.G.
Highlights: Atmospheric corrosion behaviour of welded AA6005-T6 specimens was studied. The corrosion behaviour of welds strongly depends on the size of intermetallics in stir zone. Slow welds contained relatively large Copper-rich particles along grain boundaries. The Copper-rich phases caused intergranular corrosion attack in the stir zone. Abstract: The atmospheric corrosion of extruded AA6005-T6 weldments produced with bobbin friction stir welding (BFSW) using fast and slow process parameters has been analyzed. The weldments of the same material fabricated using conventional FSW were also exposed as reference. Copper-rich phase particles were detected at the grain boundaries in the stir zone of both specimens. It was evident that the BFSW specimens exhibit better corrosion behaviour than the specimens produced using the slow process parameters. An effort was made to carefully attribute the improved corrosion resistance of the fast BFSW specimens to the difference in the microstructure of the weldments.